Issues of Digitalization and Innovation in the Educational Process - Kuvandikov, Akbar Narboevich (European Journal of Life Safety and Stability (2660-9630), 2022)
Education has been and remains in the world a significant area of development in all sectors of the national economy. And the use of digital technologies in this is one of the most important factors in obtaining and improving the quality of education. The article discusses some issues of using digital teaching technologies in educational institutions.